**i.** 3 (y + 8) = 10 (y – 4) + 8

∴ 3y + 24 = 10y – 40 + 8

∴ 3y + 24 = 10y – 32

∴ 3y + 24 – 24 = 10y – 32 – 24

**…[Subtracting 24 from both the sides] **

∴ 3y = 10y – 56

∴ 3y – 10y = 10y – 56

**…[Subtracting 10y from both the sides] **

∴ – 7y = – 56

∴ \( \cfrac{-7y}{-7}=\cfrac{-56}{-7}\)**…[Dividing both the sides by – 7]**

∴ y = 8

** ii.** \(\cfrac{x-9}{x-5} =\cfrac{5}{7}\)

**…[Multiplying both the sides by 7 (x – 5)] **

∴7 (x – 9) = 5 (x – 5)

∴7x – 63 = 5x – 25

∴7x – 63 + 63 = 5x – 25 + 63

**…[Adding 63 on both the sides] **

∴7x = 5x + 38

∴7x – 5x = 5x + 38 – 5x

**…[Subtracting 5x from both the sides] **

∴ 2x = 38

\(\cfrac{2x}{2} =\cfrac{38}{2}\)**…[Dividing both the sides by 2]**